Analysis of Disease Prevention Behavior Based on Health Belief Model (HBM) - Muhamad Rizal; Siti Aminah (YCMM, 2026)
Disease prevention behavior is an essential component of public health promotion, yet its psychological determinants require further exploration in the post-COVID-19 Malaysian context. This study analyzes factors influencing disease prevention behavior using the Health Belief Model (HBM) framework. A quantitative cross-sectional approach was applied to 320 respondents from Malaysian urban communities through purposive sampling. Analysis was conducted using SEM-PLS (SmartPLS 4.0) with 5,000 bootstrapping subsamples. Results demonstrate that self-efficacy (β=0.358, p<0.001), perceived benefits (β=0.319, p<0.001), perceived susceptibility (β=0.287, p<0.01), perceived severity (β=0.241, p<0.01), and perceived barriers (β=-0.196, p<0.05) significantly influence disease prevention behavior. Cues to action moderated the perceived susceptibility–prevention behavior relationship (β=0.143, p<0.05). The model explained 61.7% of variance (R²=0.617, Q²=0.389). Findings support individually-tailored health promotion interventions and community self-efficacy strengthening.